Kajian Literatur Profil Farmakokinetika Sacubitril-Valsartan Pada Subjek Sehat dan Gagal Jantung - Firda Amelya; Ratih Aryani; Fetri Lestari (Bandung Conference Series: Pharmacy, 2023)
Abstract. Sacubitril-Valsartan is a first-class therapeutic agent for ARNI (Angiotensin Receptor-Neprilysin Inhibitor) which can reduce blood pressure and reduce mortality and morbidity in patients with Heart failure with Reduced Ejection Fraction (HFrEF). A combination of Neprilysin inhibitors (NEPi) and Angiotensin II Receptor Blockers (ARBs) is required to reduce the increased bradykinin concentrations due to neprilysin inhibition. The success of Sacubitril-Valsartan therapy is determined by the dosage setting design taking into account pharmacokinetic factors. The pharmacokinetic profile of each individual may vary, influenced by differences in race/ethnicity, gender, age, drug interactions and physiological changes. This study aims to determine the pharmacokinetic parameters of the drug Sacubitril-Valsartan based on differences in race/ethnicity, sex, age, drug interactions, in subjects with impaired kidney function, and in subjects with heart failure. The method used for this study is the SLR (Systematic Literature Review) method. The articles used in this study were 10 journal articles obtained from the PMC database, Wiley, Springer Link. The results showed that race/ethnicity affects T1/2 longer in Caucasians, female sex has a longer T1/2, older people have a longer T1/2, Cmax, T1/2, AUC0-24h increased in impaired kidney function with decreased CL, Cmax and T1/2 increased in HFREF patients. Keywords: Pharmacokinetic, Sacubitril-Valsartan, Heart failure. Abstrak. Sacubitril-Valsartan merupakan agen terapeutik kelas pertama ARNI (Angiotensin Reseptor-Neprilysin Inhibitor) yang dapat menurunkan tekanan darah dan menurunkan mortalitas dan morbiditas pada pasien Heart failure with Reduced Ejection Fraction (HFrEF). Kombinasi Neprilysin inhibitor (NEPi) dan Angiotensin II Receptor Blockers (ARB) diperlukan untuk mengurangi konsentrasi bradikinin yang meningkat akibat penghambatan neprilysin. Keberhasilan terapi Sacubitril-Valsartan ditentukan oleh rancangan pengaturan dosis dengan mempertimbangkan faktor farmakokinetika. Profil farmakokinetika pada setiap individu dapat bervariasi dipengaruhi oleh perbedaan ras/etnis, jenis kelamin, usia, interaksi obat-obatan dan perubahan fisiologi. Penelitian ini bertujuan untuk mengetahui parameter farmakokinetika obat Sacubitril-Valsartan berdasarkan perbedaan ras/etnis, jenis kelamin, usia, interaksi obat-obatan, pada subjek dengan gangguan fungsi ginjal, dan pada subjek gagal jantung. Metode yang digunakan untuk penelitian ini adalah metode SLR (Systematic Literature Review). Artikel yang digunakan pada penelitian ini sebanyak 10 artikel jurnal yang diperoleh dari database PMC, Wiley, Springer Link. Hasil penelitian menunjukan bahwa ras/etnis mempengaruhi T1/2 lebih lama pada ras Kaukasia, jenis kelamin perempuan memiliki T1/2 lebih lama, usia tua memiliki T1/2 lebih lama, Cmax, T1/2, AUC0-24jam meningkat pada subjek gangguan fungsi ginjal dengan CL yang menurun, Cmax dan T1/2 meningkat pada pasien HFREF. Kata Kunci: Farmakokinetika, Sacubitril-Valsartan, Gagal Jantung.